Different protein localizations on the inner and outer leaflet of cell-sized liposomes using cell-free protein synthesis. Issue 1 (6th June 2018) - Uyeda, Atsuko; Watanabe, Takayoshi; Hohsaka, Takahiro; Matsuura, Tomoaki
Abstract: Membranes of living cells possess asymmetry. The inner and outer leaflets of the membrane consist of different phospholipid compositions, which are known to affect the function of membrane proteins, and the loss of the asymmetry has been reported to lead to cell apoptosis. In addition, different proteins are found on the inner and outer leaflets of the membrane, and they are essential for various biochemical reactions, including those related to signal transduction and cell morphology. While in vitro lipid bilayer reconstitution with asymmetric phospholipid compositions has been reported, the reconstitution of lipid bilayer where different proteins are localized in the inner and outer leaflet, thereby enables asymmetric protein localizations, has remained difficult. Herein, we developed a simple method to achieve this asymmetry using an in vitro transcription–translation system (IVTT). The method used a benzylguanine (BG) derivative-modified phospholipid, which forms a covalent bond with a snap-tag sequence. We show that purified snap-tagged protein can be localized to the cell-sized liposome surface via an interaction between BG and the snap-tag. We then show that IVTT-synthesized proteins can be located at the lipid membrane and that different proteins can be asymmetrically localized on the outer and inner leaflets of liposomes.